Aksiologi Filsafat Ilmu dalam Pengembangan Keilmuan - Maria Sanprayogi; Moh. Toriqul Chaer (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2017)
Humans develop a set of knowledge. This is predicated on the fact that he needs it. Because people inevitably have to determine for yourself how he behaved towards the prerequisites-a precondition of his life, and because the whole of reality is potentially took, he was in such need of accuracy and the overall integral knowledge of reality. Human beings can only live well when he responded to the reality of it as it is, and for that he should know, of the review historically, fitsafat was the one who originally handled the "knowledge" of it. Studies that increase the quantity and quality of human knowledge. Science-the science of organizing human knowledge systematically in order to be effective, and develop methods to add, deepen, and fix it. For the sake of that purpose, science should limit themselves to specific areas and develop the methods as precisely as possible to the each field.